If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x-5x+7=9-x-4
We simplify the equation to the form, which is simple to understand
3x-5x+7=9-x-4
We move all terms containing x to the left and all other terms to the right.
+3x-5x+1x=+9-4-7
We simplify left and right side of the equation.
-1x=-2
We divide both sides of the equation by -1 to get x.
x=2
| -81s^3+375z^3= | | -(34)n+1=-11 | | 5-(3)=1+2(r+3) | | -3=m | | 6x+7y=11 | | 2(3(13)+7)=-4(3-2(13)) | | a^2-15a-30=0 | | 5x+2x+7x= | | 1.80X+1.00Y=45 | | 26x+58=6x-42 | | 100=8+a | | 5x-3=12x-11 | | 18x-1(8x-7)=67 | | Two-thirdsx=-9 | | 52=2x-6(-x-2) | | f(4z)=2x^2-3 | | 21x+6=(17-26) | | 8+x=6x-47 | | x^4-4x^3-x^2+4x=0 | | 20+x^2+8x=2x | | 3(3x-1)=4(x+3)+5x | | 4x+3=7x-1 | | (x+55)=(3x-5) | | 4(7)-12=-5(7)+51 | | x^6-47x^3-8= | | 0.60x+.05(12-x)=.10(-49) | | 2(12)+2x=2(x-2)+2(16) | | 4n+2+4=-6 | | 2(3x-3)+2(x-3)=(2x-1)+(2x-1)+2x | | x^6-47x^3-8=0 | | 3c-4c+1=5+2+3 | | 4y+3y=63 |